Community learning center : the Bangladesh experience - Rahman, S. M. Mahfuzur; UNESCO Dhaka; National Seminar on Community Learning Centre (2004 : Dhaka, Bangladesh) (Dhaka : UNESCO, 2005)
Study on the activities of Community Learning Centre Project, Bangladesh; also includes papers presented at the seminar.
Includes bibliographical references (pages 89-90).
BIED
Complimentary copy from BIED
Keywords: Community Learning Center Project (Bangladesh) -- Evaluation; Community education -- Bangladesh -- Evaluation